2013
DOI: 10.1136/injuryprev-2013-040969
|View full text |Cite
|
Sign up to set email alerts
|

Firearms and suicide in US cities

Abstract: On an average day in the USA more than 100 Americans die by suicide-half use firearms. Suicide rates overall and by firearms are higher, on average, in states where household firearm ownership is more common. In general this means in states where a greater proportion of the population lives in rural areas. The current ecological study focuses on the relation between measures of household firearm prevalence and suicide mortality in urban areas (metropolitan statistical areas and divisions) using survey-based me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 24 publications
4
47
0
1
Order By: Relevance
“…The total population of KSA is 27 million with nearly 7.5 foreigners. 17 This idea is supported by studies done in Germany 18 and India 19 where hanging was the leading mode of suicide, and firearms is not that common like in the United States. It is clear that Indian fatalities are more dominant in this study as regarding to the percentage inside the total population.…”
Section: Discussionmentioning
confidence: 98%
“…The total population of KSA is 27 million with nearly 7.5 foreigners. 17 This idea is supported by studies done in Germany 18 and India 19 where hanging was the leading mode of suicide, and firearms is not that common like in the United States. It is clear that Indian fatalities are more dominant in this study as regarding to the percentage inside the total population.…”
Section: Discussionmentioning
confidence: 98%
“…Prior work has begun establishing a link between firearm ownership and increased suicide risk. Data suggest that firearm ownership is related to overall and firearm‐specific death by suicide (Anestis & Houtsma, ; Miller, Warren, Hemenway, & Azrael, ) but unrelated to thoughts of suicide (Khazem et al., ). Additionally, those who own a firearm and experience suicidal ideation are more likely to develop a plan for suicide that involves a firearm than are those who experience suicidal ideation but do not own a firearm (Betz, Barber, & Miller, ).…”
mentioning
confidence: 99%
“…Indeed, a recent meta-analysis demonstrated that our ability to predict suicide prospectively has not improved in the past half-century (Franklin et al, in press). Prominent theories (Joiner, 2005;Klonsky & May, 2015;O'Conner, 2011) argue that this failure to improve our predictive capacity stems from a tendency to focus almost entirely on variables related to thinking about suicide rather than those that facilitate the transition from suicidal ideation to suicidal behavior (Klonsky & May, 2014;Nock & Kessler, 2006;Nock et al, 2008).…”
mentioning
confidence: 99%